KEBIJAKAN DONALD TRUMP MELARANG MASUKNYA PENGUNGSI KE AMERIKA SERIKAT DITINJAU DARI KONVENSI 1951 DAN PROTOKOL 1967 TENTANG STATUS PENGUNGSI - Budyanto Budyanto; Sutiarnoto Sutiarnoto; Arif Arif (Journal of USU International Law, 2017)
ABSTRACTNowadays, the problem of refugees is a problem in our international world. The prolonged conflict in the refugee country's home has triggered a massive refugee camp. The United States under the Donald Trump government issue an executive order prohibit entry of Immigrants from 7 Muslim Majority Countries and all Refugees from any country which became a controversial policy. As the question in this paper is how the law of International Law for the refugees, how the sovereignty of a state with the binding force of International Law and the views of the 1951 Convention and 1967 Protocol against Donald Trump policy. The research used is normative juridical with descriptive nature. The data used in this study are primary legal materials, secondary legal materials and tertiary legal materials. Methods of data data using literature study. Data analysis is done qualitatively. Refugees have existed long in human civilization. Refugees are groups of vulnerable people that threatened by violence and ill-treatment by both their home country and receiving country. The regulatory arrangements for internally displaced persons are an international custom that has existed within the time of the 1951 Convention and 1967 Protocol on Refugee Status. The Sovereignty of the State and International Law are seen opposed from one another, because there is no higher power than a country. That is why, it is difficult for International Law to actually eradicate a country. The United States was a party to the 1967 Protocol, but Donald Trump issued an Executive order that prohibiting Refugees entering the United States. What Donald Trump does is unethical in international customs. America is a party to the 1967 Protocol which has agreed to under the Protocol. Should as a country ratify the Protocol, the United States obey directly on the provisions of the Conventions and this Protocol. Keywords: Refugee Protection, Refugees, 1951 Convention and 1967 Protocol, Human Rights